Iron bioaccumulation and ecological implications in the coastal swamp wetlands ecosystem of South Kalimantan: Insights from giant mudskipper fish as bioindicators - Santoso, Heri Budi; Krisdianto, Krisdianto; Yunita, Rizmi (Brawijaya University, 2024)
This study investigated iron (Fe) accumulation in South Kalimantan's coastal swamp wetlands ecosystem, utilizing giant mudskipper fish as indicators of heavy metal pollution. By analyzing Fe levels in water, sediment, and fish organs over time, insights into its effects on the environment and human health were gained. Furthermore, through Atomic Absorption Spectrometry, Fe concentrations in Kuala Lupak's coastal wetland were measured, revealing significant correlations between Fe levels in water, sediment, and fish tissues. These results enhance our understanding and inform better management strategies. Anthropogenic and natural sources contribute to the accumulation of heavy metals, particularly Fe, with anthropogenic pollution being the most dominant. This study presented the escalating concentrations of Fe within the Kuala Lupak estuary and raised concerns regarding the ecological and human health implications. Continuous monitoring, source identification, public awareness, regulations, remediation, and long-term exploration are essential for addressing heavy metal pollution and its ecological impact. Therefore, valuable insights are provided for environmental management and conservation efforts.